CFD Simulation of Pressure and Velocity Drop on Y-Type Fuel Injectors - Tarun Kumar Kotteda; Sudheer Kumar Varma Namburi; Prasada Raju Kantheti; Ravi Varma Penmetsa; Velivela Lakshmikanth Chowdary (Journal of Engineering)
Hydrocarbon injection is an important stage in combustion, where the atomisation process is involved the atomisation process which consists of disintegrating the fuel into small droplets, through an injector to add more transfer area, the fuel, through an injector to add more transfer area. The size of droplet size generated by the injector must be less than 80 μm to ensure good combustion and avoid combustion and avoid pollutants such as CO and NOx. This research worked with ethanol, a low-emission hydrocarbon, which has a high viscosity which makes it difficult to achieve the correct droplet diameter. This type of study needs to be both theoretical and experimental with simulation being a great tool to replace the latter. The finite element method included in the Flow Simulation package of the SolidWorks software was used in this research. The Flow Simulation package of the SolidWorks software was used, where a Y-type injector was sketched to be evaluated. The dynamic simulation helped to measure the velocity field, at the outlet of the air nozzle, a cavity with a diameter of 0.4 mm, which helps to increase the kinetic energy of the air. The kinetic energy of the fluid obtains the highest values of the Mach number in this area.